Cloning, Experession, and Characterization of a Laccase from the White Rot Fungi Pleurotus pulmonarius MPN18 - Quynh, Dang Thu; Hoang, Nguyen Huy; Lan, Nguyen Ngoc; Hoang, Le Viet; Nghi, Do Huu (VNU Journal of Science: Natural Sciences and Technology; Vol 39 No 2DO - 10.25073/2588-1140/vnunst.5312, 2023)
Laccase (EC 1.10.3.2) is an enzyme belonging to the polyphenol oxidase groups, which plays an important role in the oxidation of a wide variety of aromatic substrates, such as lignin, phenol, polyamine, and aryl diamines, as well as a number of other phenolic compounds or inorganic ions in the presence of oxygen. Laccase is widely applied in many different fields, especially in the textile industry, dyeing, and environmental pollution treatment. In this study, we have successfully cloned and expressed cDNA coding for laccase from Pleurotus pulmonarius MPN18 ( Pp Lac). cDNA corresponds to the gene laccase (size 1566 bp) was attached to pET 21a(+) vector and expressed in E. coli BL21, after that the enzyme was purified through HisTrap TM sp 5mL column. The purified PpLac had an activity of 899.8 U, a 74% yield with a purity of 15.2 -fold, and was tested by SDS-PAGE electrophoresis with a molecular weight of Mw = 55 kDa. Enzyme displayed optimal activity at 50 ºC and pH 4.0. Enzyme had optimal activity of 20-40 ºC after 120 min incubation and pH 4 after 6 h incubation. In future, the recombinant enzyme will be characterized for supplementation into enzyme cocktail in the treatment of lignocellulosic material.